Chemical and biomolecular analyses to discriminate three taxa of Pistacia genus from Sardinia Island (Italy) and their antifungal activity. Issue 23 (2nd December 2018) - Marengo, Arianna; Piras, Alessandra; Falconieri, Danilo; Porcedda, Silvia; Caboni, Pierluigi; Cortis, Pierluigi; Foddis, Caterina; Loi, Claudia; Gonçalves, Maria José; Salgueiro, Lígia; Maxia, Andrea
Abstract: This work reports the results and the comparison concerning the chemical and biomolecular analyses and the antifungal activity of three wild Pistacia species (Anacardiaceae) from Sardinia. Volatile oils from leaves and twigs of Pistacia x saportae, Pistacia lentiscus and Pistacia terebinthus were characterised using GC-FID and GC-MS techniques and tested against some fungal strains. Two DNA nuclear regions (ITS and 5S-rRNA-NTS) were amplified through PCR technique and sequenced. The three ** Pistacia have similar chemical profile, although there are some important quantitative differences. The analysis of ITS and 5S-rRNA-NTS regions, reveals a species-specific nucleotide variation among the three ** taxa . This method could emerge as a powerful tool for the species identification, especially because the discrimination of these three ** taxa appears difficult for non-expert botanists. Concerning the antifungal activity, P. lentiscus and P. x saportae show the highest activity against Cryptococcus neoformans, with a MIC value of 0.32 μL/mL. Abstract :